Vytautas Kavolis’s Historical Sociology (Methodological Aspects) - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 2005)
This paper examines the problematic relationship between sociology and history that had a significant place in Kavolis’s historical sociology. In light of the methodological concerns, the paper attempts to provide a conceptual introduction to Vytautas Kavolis’s historical writings. Vytautas Kavolis was a Lithuanian and American sociologist who is considered one of the founders of the civilizational analysis. Although the concept of “civilizational analysis” has deep roots in the social sciences, Kavolis points out to an urgent need to re-think it for contemporary times. His method of civilizational analysis supports an interesting pluralist perspective. Kavolis suggests a need for sociology to more thoroughly integrate sociological, historical, anthropological, psychological, and philosophical analysis into its theory and practice. He has developed an interdisciplinary method along the lines of a historical, cultural, and existential sociology. The central thesis is that although Kavolis is often regarded as an nonempirical theorist, existential empirical experience of everyday life is actually central to Kavolis’s work. The relation between sociology and history as academic disciplines is reexamined by comparing the civilizational method of Vytautas Kavolis and the approach of the traditional historiography. In contrast to a conventional historiography that centers attention upon descriptive historical facts, Kavolis urged a sociology that is historically reflexive and that is based on the existential conception of man. Kavolis‘s historical sociology is contrasted also with the theoretical attempts to build grand historical systems which narrows the “small” causal relations in history. Kavolis applies Norbert Elias’s concept of civilizing processes to problems of modernization, individualization, and humanization of human consciousness. His work is especially noteworthy when he explores the different paths of socio-historical modernization, offering a comprehensive analysis of the cultural significance of the new modes of thought and action.